2020
DOI: 10.1167/iovs.61.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Sclera Undergoes Thinning with Increasing Degree of Myopia

Abstract: Citation: Dhakal R, Vupparaboina KK, Verkicharla PK. Anterior sclera undergoes thinning with increasing degree of myopia. Invest Ophthalmol Vis Sci. 2020;61(4):6. https://doi. org/10.1167/iovs.61.4.6 PURPOSE.Considering that ocular expansion is associated with scleral thinning, this study investigated variation in scleral thickness (anterior scleral thickness [AST] and posterior scleral thickness [PST]) in different meridians across emmetropes and a wide range of myopes. METHODS.A total of 95 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
67
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 38 publications
19
67
3
Order By: Relevance
“…The distance between the cornea and the insertion site of the rectus EOM was similar to that reported previously ( Table 4 ) [ 16 – 23 ]. However, Indians have a longer average of 8.7 mm of LR and 7.3 mm of MR in the direct measurements [ 19 ].…”
Section: Discussionsupporting
confidence: 87%
“…The distance between the cornea and the insertion site of the rectus EOM was similar to that reported previously ( Table 4 ) [ 16 – 23 ]. However, Indians have a longer average of 8.7 mm of LR and 7.3 mm of MR in the direct measurements [ 19 ].…”
Section: Discussionsupporting
confidence: 87%
“…There were no significant correlations between central corneal stromal thickness and anterior scleral thickness in myopic participants. These results contrast with the recent study from Rohit Dhakal et al that suggested that the use of the anterior scleral thickness might be a biomarker for myopia progression [ 7 ]. In their study, Rohit Dhakal at al.…”
Section: Introductioncontrasting
confidence: 97%
“…Previous histomorphometric studies have demonstrated that anterior scleral thickness measured at the limbus and ora serrata was not significantly different in nonaxially elongated eyes and axially elongated eyes [5]. Buckhurst et al [14] and Pekel et al [15] also reported similar findings that axial length was not associated with the anterior scleral thickness using in vivo measurements of the sclera using optical coherence tomography (OCT), whereas more recently, Dhakal et al [16] demonstrated significant thinning of the anterior sclera along the inferior meridian with increasing axial length.…”
Section: Introductionmentioning
confidence: 89%
“…However, little attention has been given to the anterior sclera, and there is limited information in this regard. Although several studies have investigated the anterior sclera in myopic eyes, the results are conflicting [5, 14-16]. Previous histomorphometric studies have demonstrated that anterior scleral thickness measured at the limbus and ora serrata was not significantly different in nonaxially elongated eyes and axially elongated eyes [5].…”
Section: Introductionmentioning
confidence: 99%